Effect of Duration and Amplitude of Direct Current when Lidocaine Is Delivered by Iontophoresis - Ethan N. Saliba; Patrick McKeon; Christopher D. Ingeroll; Courtney L. Teeter-Heyl; Susan A. Saliba (Pharmaceutics, 2011)
Dosage for the galvanic stimulation for iontophoresis varies. Clinicians manipulate the duration or the amplitude of the current, but it is not known which is more effective. We compared the anesthetic effect of lidocaine HCL (2%) by manipulating the current parameters on 21 healthy volunteers (age: 21.2 ± 4.2, height 170.7 ± 10.2 cm, mass 82.1 ± 19.2 kg). Three conditions were administered in a random order using a Phoresor II® with 2 mL, 2% lidocaine HCL in an iontophoresis electrode. (1) HASD (40 mA*min): High amplitude (4 mA), short duration (10 min); (2) LALD (40 mA.min): Low amplitude (2 mA), long duration (20 min); (3) Sham condition (0 mA, 20 min). Semmes-Weinstein monofilament (SWM) scores were taken pre and post intervention to measure sensation changes. Two-way ANOVA with repeated measures was used to compare sensation. Both iontophoresis treatments: LALD (4.2 ± 0.32 mm) and HASD (4.2 ± 0.52 mm) significantly increased SWM scores, indicating an increase in anesthesia, compared to the sham condition (3.6 ± 0.06 mm) p < 0.05. Neither LALD nor HASD was more effective and there was no difference in anesthesia with the sham. Lidocaine delivered via iontophoresis reduces cutaneous sensation. However, there was no benefit in either a HASD or LALD treatment.